Safety and Efficacy of Cyclosporine in the Treatment of Chronic Dry Eye. (January 2014) - Schultz, Clyde
Dry-eye syndrome (DES) is a multifactorial disease affecting millions of individuals worldwide. Various factors, including age, hormonal status, genetics, sex, immune status, innervation status, nutrition, pathogens, and environmental stress, can alter the cellular and molecular structure or function of components of the ocular surface system. The resulting imbalance increases susceptibility to desiccation and epithelial damage, leading to a vicious circle in which inflammation amplifies and sustains further damage by chronic deregulation of the system. Lubricating agents and steroids have been used as treatment options. However, as the causes of the disease become better elucidated, the more chemically complex cyclosporine A has become an increasingly useful treatment option and in the United States is currently the only Food and Drug Administration (FDA)-approved prescription drug for the treatment of dry eye. The safety and efficacy of cyclosporine have been shown in numerous studies.